Chronic Comorbidities and Receipt of Breast Cancer Screening in United States and Foreign-Born Women: Data from the National Health Interview Survey - Cofie, Leslie E. (J Womens Health (Larchmt), 2019)
Objective: Research is limited on how immigrant status affects provider recommendations and adherence to breast cancer screening among women with chronic conditions. This study examined whether chronic comorbidities are associated with breast cancer screening recommendations and adherence, as well as differences between foreign-born and United States-born women. Materials and Methods: The study examined data from the 2013 and 2015 National Health Interview Survey on women 50–74 years of age (N = 12,425). Chi-square analysis was used to assess relationships between chronic comorbidities (hypertension, diabetes, and obesity) and mammography screening recommendation and adherence (screened in the last 3 years). Multivariable binary logistic regression analysis examined the relationship between foreign-born status and mammography screening, adjusting for provider screening recommendation and chronic comorbidities. Results: Obesity and hypertension were positively associated with mammography screening recommendation and adherence (p < 0.05). United States-born women, compared with foreign-born women, had higher rates of obesity (28% vs. 24%, p < 0.001) and hypertension (44% vs. 41%, p < 0.001). Compared with normal-weight women, underweight women (odds ratio [OR]: 0.57, confidence interval [CI]: 0.39–0.82) were significantly less likely to report receiving mammograms. In stratified analyses, foreign-born underweight women (OR: 0.25, CI: 0.09–0.68) remained less likely to report receiving mammograms after controlling for years lived in the United States and citizenship status. Conclusion: Public health intervention efforts must encourage mammography screening for both United States-born and foreign-born women, especially those diagnosed with chronic conditions.